Current Concepts in Aesthetic Laser Medicine The 694 Nm Q Switched Ruby Laser - Peter Arne Gerber; Said Hilton (European Medical Journal, 2014)
Quality-switched (q-switched) laser systems are the gold standard for the treatment of benign pigmented lesions and tattoo removal. A frequently used system is the q-switched ruby laser that emits monochromatic light at the wavelength of 694 nm. This system is used for the removal of age spots (senile lentigines), seborrhoeic keratosis, tattoos, and other dyschromatoses. The increasing need for the removal of, for example, age spots and unwanted tattoos, reflects both the wish of our ageing society to preserve a youthful appearance and the steadily growing prevalence of tattoos. This review highlights the potential, limitations, and novel treatment concepts of using q-switched ruby laser systems.